Genome mining in Trichoderma viride J1-030: discovery and identification of novel sesquiterpene synthase and its products - Sun, Xiang; Cai, You-Sheng; Yuan, Yujie; Bian, Guangkai; Ye, Ziling; Deng, Zixin; Liu, Tiangang (Beilstein Journal of Organic Chemistry, 2019)
Sesquiterpene synthases in Trichoderma viride have been seldom studied, despite the efficiency of filamentous fungi for terpenoid production. Using the farnesyl diphosphate-overexpressing Saccharomyces cerevisiae platform to produce diverse terpenoids, we herein identified an unknown sesquiterpene synthase from T. viride by genome mining and determined the structure of its corresponding products. One new 5/6 bicyclic sesquiterpene and its esterified derivative were characterised by GC–MS and 1D and 2D NMR spectroscopy. To the best of our knowledge, this is the first well-identified sesquiterpene synthase from T. viride to date.
Keywords: genome mining; metabolic engineering; natural products; sesquiterpene synthase; terpenes; Trichoderma viride J1-030

(untitled) - Bian, G. K.; Ma, T.; Liu, T. G. (Methods Enzymol., 2018)

(untitled) - Huber, T.; Weisheit, L.; Magauer, T. (Beilstein J. Org. Chem., 2015)

(untitled) - Christianson, D. W. (Chem. Rev., 2017)

(untitled) - Pemberton, T. A.; Chen, M.; Harris, G. G.; Chou, W. K. W.; Duan, L.; Köksal, M.; Genshaft, A. S.; Cane, D. E.; Christianson, D. W. (Biochemistry, 2017)

(untitled) - Lauterbach, L.; Rinkel, J.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Huang, A. C.; Hong, Y. J.; Bond, A. D.; Tantillo, D. J.; Osbourn, A. (Angew. Chem., Int. Ed., 2018)

(untitled) - Bian, G.; Rinkel, J.; Wang, Z.; Lauterbach, L.; Hou, A.; Yuan, Y.; Deng, Z.; Liu, T.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Yang, Y.-l.; Zhang, S.; Ma, K.; Xu, Y.; Tao, Q.; Chen, Y.; Chen, J.; Guo, S.; Ren, J.; Wang, W.; Tao, Y.; Yin, W.-B.; et al. (Angew. Chem., Int. Ed., 2017)

(untitled) - Köksal, M.; Jin, Y.; Coates, R. M.; Croteau, R.; Christianson, D. W. (Nature, 2011)

(untitled) - Rabe, P.; Rinkel, J.; Nubbemeyer, B.; Köllner, T. G.; Chen, F.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2016)

(untitled) - Peng, B.; Plan, M. R.; Chrysanthopoulos, P.; Hodson, M. P.; Nielsen, L. K.; Vickers, C. E. (Metab. Eng., 2017)

(untitled) - Matsuda, Y.; Mitsuhashi, T.; Quan, Z.; Abe, I. (Org. Lett., 2015)

(untitled) - Kim, D.; Lee, E.; Lee, J.; Leutou, A.; Shin, Y.-H.; Choi, B.; Hwang, J.; Hahn, D.; Choi, H.; Chin, J.; Cho, S.; Hong, Y.; et al. (Mar. Drugs, 2018)

(untitled) - Klapschinski, T. A.; Rabe, P.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2016)

(untitled) - Ye, Y.; Minami, A.; Mandi, A.; Liu, C.; Taniguchi, T.; Kuzuyama, T.; Monde, K.; Gomi, K.; Oikawa, H. (J. Am. Chem. Soc., 2015)

(untitled) - Nakano, C.; Kudo, F.; Eguchi, T.; Ohnishi, Y. (ChemBioChem, 2011)

(untitled) - Hu, Y.; Chou, W. K. W.; Hopson, R.; Cane, D. E. (Chem. Biol., 2011)

(untitled) - Cao, L.; Shehla, N.; Tasneem, S.; Cao, M.; Sheng, W.; Jian, Y.; Li, B.; Peng, C.; Choudhary, M. I.; Atta-ur-Rahman; Liao, D.-f.; Wang, W. (Molecules, 2019)

(untitled) - Yan, Y.; Liu, Q.; Zang, X.; Yuan, S.; Bat-Erdene, U.; Nguyen, C.; Gan, J.; Zhou, J.; Jacobsen, S. E.; Tang, Y. (Nature, 2018)

(untitled) - Minami, A.; Ozaki, T.; Liu, C.; Oikawa, H. (Nat. Prod. Rep., 2018)

(untitled) - Bian, G.; Hou, A.; Yuan, Y.; Hu, B.; Cheng, S.; Ye, Z.; Di, Y.; Deng, Z.; Liu, T. (Org. Lett., 2018)

(untitled) - Mannina, L.; Segre, A. L.; Ritieni, A.; Fogliano, V.; Vinale, F.; Randazzo, G.; Maddau, L.; Bottalico, A. (Tetrahedron, 1997)

(untitled) - John, R. P.; Tyagi, R. D.; Prévost, D.; Brar, S. K.; Pouleur, S.; Surampalli, R. Y. (Crop Prot., 2010)

(untitled) - Bian, G.; Deng, Z.; Liu, T. (Curr. Opin. Biotechnol., 2017)

(untitled) - Peng, B.; Nielsen, L. K.; Kampranis, S. C.; Vickers, C. E. (Metab. Eng., 2018)

(untitled) - Yap, H.-Y. Y.; Muria-Gonzalez, M. J.; Kong, B.-H.; Stubbs, K. A.; Tan, C.-S.; Ng, S.-T.; Tan, N.-H.; Solomon, P. S.; Fung, S.-Y.; Chooi, Y.-H. (Microb. Cell Fact., 2017)

(untitled) - Kubicek, C. P.; Herrera-Estrella, A.; Seidl-Seiboth, V.; Martinez, D. A.; Druzhinina, I. S.; Thon, M.; Zeilinger, S.; Casas-Flores, S.; Horwitz, B. A.; Mukherjee, P. K.; Mukherjee, M.; Kredics, L.; et al. (Genome Biol., 2011)

(untitled) - Martinez, D.; Berka, R. M.; Henrissat, B.; Saloheimo, M.; Arvas, M.; Baker, S. E.; Chapman, J.; Chertkov, O.; Coutinho, P. M.; Cullen, D.; Danchin, E. G. J.; Grigoriev, I. V.; et al. (Nat. Biotechnol., 2008)

(untitled) - Yuan, Y.; Litzenburger, M.; Cheng, S.; Bian, G.; Hu, B.; Yan, P.; Cai, Y.; Deng, Z.; Bernhardt, R.; Liu, T. (ChemBioChem, 2019)

(untitled) - Burkhardt, I.; Siemon, T.; Henrot, M.; Studt, L.; Rösler, S.; Tudzynski, B.; Christmann, M.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2016)

(untitled) - Burkhardt, I.; Kreuzenbeck, N. B.; Beemelmanns, C.; Dickschat, J. S. (Org. Biomol. Chem., 2019)

(untitled) - Gallo, A.; Mulè, G.; Favilla, M.; Altomare, C. (Physiol. Mol. Plant Pathol., 2004)

(untitled) - Crutcher, F. K.; Parich, A.; Schuhmacher, R.; Mukherjee, P. K.; Zeilinger, S.; Kenerley, C. M. (Fungal Genet. Biol., 2013)

(untitled) - Zhu, F.; Zhong, X.; Hu, M.; Lu, L.; Deng, Z.; Liu, T. (Biotechnol. Bioeng., 2014)

(untitled) - Hu, D.-B.; Zhang, S.; He, J.-B.; Dong, Z.-J.; Li, Z.-H.; Feng, T.; Liu, J.-K. (Fitoterapia, 2015)

(untitled) - Iliopoulou, D.; Vagias, C.; Galanakis, D.; Argyropoulos, D.; Roussis, V. (Org. Lett., 2002)

(untitled) - Takino, J.; Kozaki, T.; Sato, Y.; Liu, C.; Ozaki, T.; Minami, A.; Oikawa, H. (J. Am. Chem. Soc., 2018)

(untitled) - Wawrzyn, G. T.; Quin, M. B.; Choudhary, S.; López-Gallego, F.; Schmidt-Dannert, C. (Chem. Biol., 2012)